Tolaki Mekongga Cultural Universal Monograph Development to High School Students Local Culture Understanding - Nur Ihsan HL; Robert Sibarani; Sarmadan; Nasruddin; Andri Estining Sejati (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
There is a lack of learning resources about the Tolaki Mekongga culture in the school curriculum that are needed for the preservation of local cultural identity. It is necessary to develop a cultural monograph based on local elements that are relevant and appropriate to the educational context as a means of cultural literacy for students. This study aims to determine the effectiveness of developing a universal cultural monograph of the Tolaki Mekongga community on the understanding of the local culture of high school students. The study used the Borg and Gall model, which involved ethnographic data collection, expert validation, and field testing. Small group subjects were 40 students spread across two public and two private high schools. The large group subjects were 200 students spread across the four schools in grade IX. Observation, interviews, questionnaires, written tests, and documentation were used for data collection. Data analysis was carried out using descriptive statistical analysis with a Likert scale, percentages, and scoring. The use of the monograph improves students' understanding of local culture. This research highlights the potential of integrating local cultural content into the formal education curriculum, contributing to cultural preservation and character education amidst the challenges of globalization. The research implications contribute theoretically to the development of universal cultural elements into educational frameworks. The practical implications provide a model of cultural monographs that can be adopted in school curricula as an effective tool for preserving students' local cultures.